Aspekte des Zusammenlebens zwischen Muslimen und Nichtmuslimen - Kokew, Stephan Matthias (Islam II. Regionen, Lebensformen, Geistesgeschichte)
Keywords: Islam; Islamwissenschaft; Toleranz; Islamische Geistesgeschichte; Interreligiöser Dialog

Assessment of Fibre-Matrix Adhesion in Reinforced Polymers by Modal Damping of Guided Acoustic Waves - Claes, Leander; Zeipert, Henning; Brandes, Philipp; Moritzer, Elmar; Henning, Bernd

Zeit für Arbeitszufriedenheit? Eine quantitativ-empirische Studie zur Bedeutung fester Kooperationszeiten für die Arbeitszufriedenheit von Lehrkräften in inklusiven Schulen - Wohnhas, Verena; Neumann, Phillip; Lütje-Klose, Birgit (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Die Arbeitszufriedenheit von Lehrkräften gilt als zentrale Komponente für die Qualität des Bildungssystems. In inklusiven Schulen müssen Regelschullehrkräfte und sonderpädagogische Lehrkräfte kooperieren, um allen Schüler:innen eine bestmögliche Förderung zu gewährleisten. Dazu benötigen sie jedoch Zeitfenster, die von vielen Lehrkräften als nicht ausreichend benannt werden. Ziel des vorliegenden Beitrags ist es, empirisch zu untersuchen, welche Bedeutung festen Zeitfenstern für die Lehrkräftekooperation im Klassenteam, im Jahrgangsteam und im Fachteam für die Arbeitszufriedenheit zukommt. Weiterhin soll überprüft werden, ob Teile der Zusammenhänge über die Zufriedenheit mit der Kooperationshäufigkeit und die kollektive Selbstwirksamkeitsüberzeugung der Lehrkräfte erklärt werden können. Dazu werden Daten aus dem BMBF-geförderten Projekt BiFoKi mit N=194 Lehrkräften und N=28 Schulleitungen analysiert. Die Ergebnisse zeigen, dass feste Zeitfenster für die Kooperation in den unterschiedlichen Teams mit einer erhöhten Arbeitszufriedenheit im Zusammenhang stehen und in Teilen über die kollektive Selbstwirksamkeitsüberzeugung mediiert werden.
Keywords: Arbeitszufriedenheit; Inklusion; Sonderpädagogik; Kooperation; Selbstwirksamkeit; Schulentwicklung; job satisfaction; Inclusion; Special Education; Self-efficacy; school development

Digitale Medien in der Lehrer-Schüler-Interaktion - Herzig, Bardo (Lehrer-Schüler-Interaktion. Inhaltsfelder, Forschungsperspektiven und methodische Zugänge)

Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen

Sustainability, Climate Change and Convention Theory - Lenz, Sarah (Handbook of Economics and Sociology of Conventions)

„The folk songs of America“ und „complex female characters on stage“: Musikgeschichtliche Wendepunkte in den Komponistinnenbiografien von Florence Price and Mizzy Mazzoli - Tumat, Antje (her:voice. Komponistinnenfestival 2024)

Empirische Methoden der psychologiedidaktischen Forschung - Scharlau, Ingrid; Seifert, Andreas (Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen: Ein Lehrbuch mit Unterrichtsmaterialien)

Psychologiedidaktik durch Analyse von Kommunikation - Scharlau, Ingrid; Patrzek, Justine; Schreiber, Christine (Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen: Ein Lehrbuch mit Unterrichtsmaterialien)

Schreiben im Psychologieunterricht unterstützen - Scharlau, Ingrid; Christine, Schreiber (Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen: Ein Lehrbuch mit Unterrichtsmaterialien)

From One to Three? The Viability of Emergent Social Trinitarianism - Grössl, Johannes (Engaging Nicene Trinitarianism. Historical Analysis, Theological Exploration, and Contemporary Relevance)
In “From One to Three?”, Johannes Grössl explores the 4th-century Trinitarian theory of Marcellus of Ancyra, proposing Emergent Social Trinitarianism as a modern paradigm. According to this theory, a primordial God became a Trinitarian God by freely choosing to be love or by freely creating a world to which He is related through a loving relationship. This model envisions God as an eternal primordial being who, through creation and incarnation, becomes a Trinity of three fully divine persons. Two persons (the Second and the Third) relinquish aspects of their divinity, becoming dependent on the First, while all three engage temporally in creation: the Father interacts with His creatures, the Son transforms in His earthly life (Hebr 5:8), and the Spirit proceeds from their mutual love. Grössl positions Marcellus’ theory as an alternative to Latin and Social Trinitarianism, addressing key theological challenges such as divine temporality, relationality, and immutability. By blending historical and contemporary insights, this study highlights the enduring relevance of Marcellus’ thought for Trinitarian speculation and Christian tradition.

Zur lehrkräftegelenkten Digitalisierung fachsprachlich orientierten DaF-Unterrichtsmaterials - Prikoszovits, Matthias (Digitale Lehr-/Lernressourcen und digitale Kompetenz. Forschung aus dem Hochschulkontext.)

Trim turnpikes for optimal control problems with symmetries - Flaßkamp, Kathrin; Maslovskaya, Sofya; Ober-Blöbaum, Sina; Wembe Moafo, Boris Edgar (Mathematics of Control, Signals, and Systems)
Abstract Motivated by mechanical systems with symmetries, we focus on optimal control problems possessing certain symmetries. Following recent works (Faulwasser in Math Control Signals Syst 34:759–788 2022; Trélat in Math Control Signals Syst 35:685–739 2023), which generalized the classical concept of static turnpike to manifold turnpike we extend the exponential turnpike property to the exponential trim turnpike for control systems with symmetries induced by abelian or non-abelian groups. Our analysis is mainly based on the geometric reduction of control systems with symmetries. More concretely, we first reduce the control system on the quotient space and state the turnpike theorem for the reduced problem. Then we use the group properties to obtain the trim turnpike theorem for the full problem. Finally, we illustrate our results on the Kepler problem and the rigid body problem.

Der Morgenimpuls als Grenzgänger. Praxeologische Rekonstruktionen des Profilindikators Katholischer Schulen - Reis, Oliver; Walter, Marie; Frieler, Jana

Forging the LongSWORD: Exaptation and Enhancement of the SWORD Framework for Workaround Detection - Löhr, Bernd; Bartelheimer, Christian; Köhne, Frank; Nordlohne, Sina; Alile, Daniel; Latten, Andrees (Business Process Management Workshops)

Neural Network Inference in High-Performance Computing: Closing the Gap for FINN based Reconfigurable Accelerators - Jungemann, Linus; Wintermann, Bjarne; Riebler, Heinrich; Plessl, Christian (Proceedings of the 2025 ACM/SIGDA International Symposium on Field Programmable Gate Arrays)

Adaptive DC-Link Voltage Control for 22 kW, 40 kHz LLC Resonant Converter Considering Low-Frequency Voltage Ripple - Unruh, Roland; Böcker, Joachim; Schafmeister, Frank (Electronics)
The LLC converter achieves the highest efficiency in resonant operation. Conventionally, the input DC-link voltage is controlled to operate the LLC converter at resonance for the given operating point. However, the DC-link capacitor voltage shows a low-frequency voltage ripple (typically the second harmonic of grid frequency) in cascaded converters so that the LLC has to adapt its switching frequency within the grid period. Conventionally, the LLC converter operates 50% of the time above the resonant frequency of 40 kHz and 50% below resonance. Both operating conditions cause additional losses. However, experimental measurements indicate that the below-resonance operation causes significantly higher losses than above-resonance operation due to much higher primary and secondary transformer currents. It is better to increase the DC-link voltage by 30% of the peak-to-peak low-frequency voltage ripple to mostly avoid below-resonance operation (i.e., from 650 V to 680 V in this case). With the proposed control, the LLC converter operates about 75% of time over resonance and only 25% of time below resonance. The overall efficiency increases from 97.66% to 97.7% for the average operating point with an 80% load current. This corresponds to a 2% total loss reduction. Finally, the peak resonance capacitor voltage decreases from 910 V to 790 V (−13%).
Keywords: adaptive DC-link voltage; cascaded H-bridge; resonant operation; Full-Bridge Converter; loss minimization; LLC Resonant Converter; peak capacitor voltage reduction

Information dissemination and confusion in signed networks - Jin, Ligang; Steffen, Eckhard (Discrete Applied Mathematics)
We introduce a model of information dissemination in signed networks. It is a discrete-time process in which uninformed actors incrementally receive information from their informed neighbors or from the outside. Our goal is to minimize the number of confused actors — that is, the number of actors who receive contradictory information. We prove upper bounds for the number of confused actors in signed networks and in equivalence classes of signed networks. In particular, we show that there are signed networks where, for any information placement strategy, almost 60% of the actors are confused. Furthermore, this is also the case when considering the minimum number of confused actors within an equivalence class of signed graphs.

Digitale Kompetenzen von Schüler:innen und Rahmenbedingungen des Kompetenzerwerbs in Nordrhein-Westfalen - Drossel, Kerstin; Niemann, Jan; Eickelmann, Birgit; Niggemeier, Johannes Bernd (SchulVerwaltung Nordrhein-Westfalen)

Europäische Bildungsinitiativen als Rahmen medienpädagogischer Professionalisierung in der Erwachsenenbildung. Rekonstruktive Analysen zum Medien(bildungs)begriff - Bellinger, Franziska; Dehmel, Lukas (Perspektiven auf Bildung in Europa. Festschrift für Beatrix Niemexer-Jensen.)